Volatility, information feedback and market microstructure noise: A tale of two regimes - Torben G. Andersen; Gökhan Cebiroglu; Nikolaus Hautsch (Goethe University Frankfurt, Center for Financial Studies (CFS), 2017)
We extend the classical "martingale-plus-noise" model for high-frequency prices by an error correction mechanism originating from prevailing mispricing. The speed of price reversal is a natural measure for informational efficiency. The strength of the price reversal relative to the signal-to-noise ratio determines the signs of the return serial correlation and the bias in standard realized variance estimates. We derive the model's properties and locally estimate it based on mid-quote returns of the NASDAQ 100 constituents. There is evidence of mildly persistent local regimes of positive and negative serial correlation, arising from lagged feedback effects and sluggish price adjustments. The model performance is decidedly superior to existing stylized microstructure models. Finally, we document intraday periodicities in the speed of price reversion and noise-to-signal ratios.
urn:nbn:de:hebis:30:3-430076
Keywords: C58; C32; G14; 330; volatility estimation; market microstructure noise; price reversal; momentum trading; contrarian trading